Desensitized chimeric antigen receptor T cells selectively recognize target cells with enhanced antigen expression - Chungyong Han (Nature Portfolio, 2018)
Engineered T cells with chimeric antigen receptor (CAR) are emerging as an effective cancer therapy. Here the authors show that CAR T cells recognizing self-MHC can be ‘tuned’ ex vivo via CAR downregulation and CAR T cell death to generate a CAR T pool specifically targeting tumor cells with high MHC expression.